Integrable CMOS sinusoidal frequency doubler and full-wave rectifier - Surakampontorn, Wanlop; Riewruja, Vanchai (My University, 1992)
A CMOS integrable circuit technique for the realization of both a sinusoidal frequency doubler and a full-wave rectifier is described in this paper. The realization method makes use of the characteristic of a simple CMOS class AB amplifier configuration. Simulation and experimental results demonstrating the circuit performance are also included. © 1992 Tayor and Francis Ltd.